Myotonic dystrophy and craniofacial morphology: clinical and instrumental study - Portelli, M; Matarese, G; Militi, A; Nucera, R; Triolo, G; Cordasco, G (European journal of paediatric dentistry, 2009)
The aim of this study is to assess if, and to what extent, myotonic dystrophy can affect the craniofacial growth pattern. The research was conducted on a sample of 27 patients with Steinert's myotonic dystrophy (study group). Each subject underwent a clinical examination with impression-taking and intra- and extraoral photographs. A latero-lateral projection teleradiography in the mirror position was also taken and a cephalometric examination was performed. The assessed values were compared with those obtained from a group of healthy subjects (control group). Statistical analysis of the data obtained from the myotonic patients who developed the disease during the growth phase revealed alterations in the transversal plane and, to an even greater extent, the vertical one, with a high frequency of anterior open bite. Discussion and conclusions Regarding the pathogenesis of these types of skeletal dysplasias, the authors hypothesise a posterior rotation growth pattern, resulting from gravitational force prevailing over the deficit of the elevator muscles.